A emissão de CO₂, o consumo de energia renovável e o crescimento econômico: uma análise para o Brasil, 1990 - 2018 - Basso, Cassiane Gris (2022)
Economic growth contributes to increase CO₂ emissions; on the other hand, renewable energy is beneficial to the environment. This research aims to investigate the relationship among CO₂ emissions, economic growth (GDP) and energy consumption for Brazil from 1990 to 2018. Therefore, annual data were used according to the data availability from the World Bank, according to the World Development Indicators, for variables such as CO₂ emission, GDP, and those ones related to data from the International Energy Agency for the variable consumption of renewable energy. Furthermore, the VECM methodology was used, which is a method that has been often used for time series; it treats all variables as endogenous and examines the interaction among them. This study recorded that changes in GDP caused a directly proportional effect on CO₂ emissions, a positive change in GDP causes the same movement in CO₂ emissions. Meanwhile, changes in renewable energy consumption have an inversely proportional effect on CO₂ emissions, which meant that, a positive change in renewable energy consumption leads to a negative change in CO₂ emissions. These considerations point to the answer to the research problem about the relationship among CO₂ emission, energy consumption and economic growth. This research contributes to the existing literature on the variables and provides a perspective on CO₂ emissions, renewable energy consumption and economic growth for Brazil in the current context.